Mitochondrial genome of Abraxas suspecta (Lepidoptera: Geometridae) and comparative analysis with other Lepidopterans - Sun, Yu; Zhang, Jiawei; Li, Qingqing; Liang, Dan; Abbas, Muhammad Nadeem; Qian, Cen; Wang, Lei; Wei, Guoqing; Zhu, Bao-Jian; Liu, Chao-Liang (Zootaxa, 2017)
In this study, a complete mitochondrial genome (mitogenome) sequence of Abraxas suspecta (Lepidoptera: Geometridae) is isolated and characterized. The complete DNA is 15,547 bp length and contains 2 ribosomal RNA genes, 23 putative transfer RNA (tRNA) genes including an extra tRNAAsn (AUU), 13 protein-coding genes and an adenine (A) + thymine (T)-rich region. The nucleotide composition and gene organization are identical to those of other lepidopteran, except for the presence of an extra copy of trnN (AUU). Of the 38 genes, twenty-five genes (9 PCGs and 16 tRNAs) are encoded by heavy strand (H-strand), while thirteen are encoded by light strand (L-strand). Among the 13 PCGs, 12 PCGs employ ATN as initiation codon, while cytochrome c oxidase subunit 1 (cox1) utilizes CGA as initiation codon. Four of the 13 PCGs have the incomplete termination codon T, while the remainder terminated with the canonical stop codon. All tRNA genes are folded into the typical clover-leaf structure of mitochondrial tRNAs, except for the tRNASer (AGN) gene, in which the DHU arm fails to form a stable stem-loop structure. The A+T-rich region is 532 bp long, and contains some conserved regions, including ‘ATAGA’ motif followed by a 17bp poly-T stretch, a microsatellite-like element (AT)8(AAT)3 and also a poly-A element. A short Phylogenetic analysis based on 13 PCGs using maximum likelihood (ML) and Bayesian inference (BI) revealed that A. suspecta resides in the Geometridae family. We present the method and approach to use moths as model organisms for further genetic and evolutionary biology studies.